2008
DOI: 10.1002/nau.20583
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of tolterodine with vaginal estrogen cream versus tolterodine alone for the treatment of postmenopausal women with overactive bladder syndrome

Abstract: A combination of vaginal estrogen cream and tolterodine is a potential therapy for postmenopausal women with OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 29 publications
0
42
0
3
Order By: Relevance
“…A controlled study of 229 femmes presenting an overactive detrusor did not show any benefit for topical vaginal oestrogen therapy associated with tolterodine versus tolterodine alone for overactive bladder symptoms (LE2) [29]. Another randomised controlled trial in 80 women with overactive bladder syndrome, also comparing the effect of topical vaginal oestrogen therapy associated with tolterodine with that of tolterodine alone, found a significant improvement of objective parameters and quality of life when oestrogens were associated with tolterodine (LE2) [30]. Finally, a recent randomised trial comparing the efficiency of topical vaginal oestrogen therapy with that of oxybutynin for the treatment of overactive bladder syndrome found that the two products were similar in terms of efficiency (LE2) [31].…”
Section: Data Obtained From Random Studies Of Women Treated For Urinamentioning
confidence: 99%
“…A controlled study of 229 femmes presenting an overactive detrusor did not show any benefit for topical vaginal oestrogen therapy associated with tolterodine versus tolterodine alone for overactive bladder symptoms (LE2) [29]. Another randomised controlled trial in 80 women with overactive bladder syndrome, also comparing the effect of topical vaginal oestrogen therapy associated with tolterodine with that of tolterodine alone, found a significant improvement of objective parameters and quality of life when oestrogens were associated with tolterodine (LE2) [30]. Finally, a recent randomised trial comparing the efficiency of topical vaginal oestrogen therapy with that of oxybutynin for the treatment of overactive bladder syndrome found that the two products were similar in terms of efficiency (LE2) [31].…”
Section: Data Obtained From Random Studies Of Women Treated For Urinamentioning
confidence: 99%
“…[30], прово-дивших лечение 80 пациенток с ГМП, показана достовер-ная предпочтительность применения комбинации толте-родина и вагинальных форм эстрогенов по сравнению с использованием только толтеродина.…”
Section: треугольник льето 40unclassified
“…One study evaluating the combination of tolterodine and conjugated equine estrogen cream reported that the combination was associated with significant improvements in daytime frequency and voided volume (but not nocturia, urgency or urgency incontinence) compared to tolterodine alone. 15 The investigators of another study, which evaluated tolterodine with or without oestriol cream, reported that there was no difference between arms in any of the efficacy endpoints. 16 Subjects all had detrusor overactivity rather than just symptoms of OAB.…”
Section: Estrogensmentioning
confidence: 99%